Environmental Disclosure as a Tool for Public Sector Legitimacy: A Twitter Intelligence Approach. - Bonsón, Enrique; Perea-Khalifi, David; Bednárová, Michaela (IGI Global, 2020)
The purpose of this study is to measure the extent of Twitter environmental reporting by Andalusian municipalities (Spain) and identify the determinant factors of such a disclosure. Thus, factors such as population, geolocation, political signs, and sustainable commitments were analyzed under the legitimacy theory approach. The sample consisted of the official Twitter accounts of the 153 biggest local governments in Andalusia. The classification of the environmental tweets was based on a dictionary based on the GRI reporting standards for environmental disclosure, and a Twitter environmental disclosure index (TEDI) was developed. The results show that most of the local governments in Andalusia (77.78%) have an official Twitter account with different levels of audience, penetration, and activity. On the other hand, it was found that environmental disclosure is very low. However, municipalities with more surplus budget and municipalities with a greater number of sustainable commitments networks tend to report more on environmental issues through Twitter.
Keywords: Administración local - Andalucía; Medio ambiente; Redes sociales en Internet; Twitter; Environmental disclosure; GRI reporting; Legitimacy theory; Local government